2021
DOI: 10.1111/jmft.12491
|View full text |Cite
|
Sign up to set email alerts
|

Online relationship education programs improve individual and relationship functioning: A meta‐analytic review

Abstract: Online access to relationship enhancing educational resources are needed now more than ever, and there is a growing number of available programs for couples to choose. But, what is the evidence that these programs improve individual and relationship well‐being? We conducted a meta‐analysis, using random‐effects, examining individual and relationship outcomes of online relationship education programs. We identified 12 publications included in the analysis, and found that online relationship education programs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…(The dosage difference was confounded by the highest dosage studies all being in the OPRE study group, so this finding should be interpreted cautiously.) Also, online programs (that were some of the lowest dosage programs reviewed) produced some of the largest effect sizes in this study (d = .26, k = 4) and in studies of online programs not reviewed here (see Spencer & Anderson, 2021). Doss, Knopp et al (2020) have speculated that online delivery of CRE attracts couples with greater motivation to improve their relationship (in the "action" stage of change) and gets the intervention to them in a more timely way.…”
Section: Moderators Of Program Effectsmentioning
confidence: 59%
“…(The dosage difference was confounded by the highest dosage studies all being in the OPRE study group, so this finding should be interpreted cautiously.) Also, online programs (that were some of the lowest dosage programs reviewed) produced some of the largest effect sizes in this study (d = .26, k = 4) and in studies of online programs not reviewed here (see Spencer & Anderson, 2021). Doss, Knopp et al (2020) have speculated that online delivery of CRE attracts couples with greater motivation to improve their relationship (in the "action" stage of change) and gets the intervention to them in a more timely way.…”
Section: Moderators Of Program Effectsmentioning
confidence: 59%
“…The results indicated that the perceived quality of the partner's response to one's own COVID‐related stress predicted relationship satisfaction maintenance pre‐ to post‐COVID outbreak. Therefore, interventions aimed at strengthening partners' responsiveness and dyadic coping may be useful for partners when traversing these difficult times, especially approaches that can be delivered through a self‐directed, online platform (Spencer & Anderson, 2021 ), which is better suited to social‐distancing regulations. For example, Bodenmann and Shantinath ( 2004 ) developed an empirically based dyadic skill‐learning intervention targeting partners' dyadic coping.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing distressed and disrupted partnerships as key insertion points for men’s mental health promotion programs is critical. Upstream, as Spencer and Anderson (2021) suggest, there are protective benefits in equipping men with relationships skills through online programs. Herewith, we might reduce the potential for dire mental illness outcomes through prevention as well as anticipating and supporting men through the mental health challenges that are known to accompany relationship break-ups.…”
Section: Discussionmentioning
confidence: 99%